HIDDEN POTENTIAL OF CHILDREN’S ART EXHIBITIONS AND THEIR IMPACT ON THE INCREASE IN TEACHER’S SELF-EFFICACY - Stepankova, Katerina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
A key element contributing to the quality of teaching in all educational areas is teacher’s belief in their professional competencies. The paper describes the impact of high or low teacher’s self-efficacy beliefs on the quality of their teaching, as well as the ways to promote self-efficacy. We see a gap in knowledge regarding the issue of whether kindergarten teachers are able to recognise the sources of self-efficacy offered by their practice. The aim of the research was to find out whether teachers can use the potential of children's art exhibitions to strengthen their teacher’s self-efficacy, not only to present children's art works. A qualitative approach has been applied to the research that involved 30 kindergarten teachers awarded for an excellent level of art education. The research has shown that even the most highly qualified teachers benefit from the exhibition in terms of being professionally inspired and motivated. These are mainly self-efficacy supports in the category of vicarious experience and social persuasion. The impact of perceived personal well-being is also very significant. These findings highlight the importance of self-evident activities, such as the presentation and exhibition of children's art works. They can thus serve as a guide in the conception of exhibitions and conscious support for teacher’s self-efficacy.